2000
DOI: 10.1210/en.141.3.980
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Endocrine Systems and Food Intake by Green Tea Epigallocatechin Gallate

Abstract: Green tea polyphenols, especially the catechin, (-)-epigallocatechin gallate (EGCG), have been proposed as a cancer chemopreventative based on a variety of laboratory studies. For clear assessment of the possible physiological effects of green tea consumption, we injected pure green tea catechins ip into rats and studied their acute effects on endocrine systems. We found that EGCG, but not related catechins, significantly reduced food intake; body weight; blood levels of testosterone, estradiol, leptin, insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(166 citation statements)
references
References 0 publications
8
152
3
3
Order By: Relevance
“…In addition to possessing antiviral [6][7][8] and immunostimulatory [9][10][11][12] properties, catechins also exhibit antitumor [13][14][15][16] and antioxidative 11,17 effects. There is also sufficient evidence for antiangiogenic activity.…”
Section: Biologic Properties Of Green Tea Catechinsmentioning
confidence: 99%
“…In addition to possessing antiviral [6][7][8] and immunostimulatory [9][10][11][12] properties, catechins also exhibit antitumor [13][14][15][16] and antioxidative 11,17 effects. There is also sufficient evidence for antiangiogenic activity.…”
Section: Biologic Properties Of Green Tea Catechinsmentioning
confidence: 99%
“…Similar studies by Yang and Koo 12 have shown that Chinese jasmine green tea has significant serum-and liver-cholesterol lowering effects. Kao et al 13 reported that injection of the tea polyphenol EGCG into mice reduced their food intake and body weight, but the mechanism remains to be elucidated. Recently, an in vitro study has shown that EGCG is an effective inhibitor of FAS isolated from chicken liver.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an in vitro study has shown that EGCG is an effective inhibitor of FAS isolated from chicken liver. 13 It seems that because most previous studies on the FAS inhibitors have been confined to their inhibitory effects on the enzyme activity of FAS, 5,7,8,14 it would be more interesting to investigate the inhibitory effects of these compounds on the enzyme biosynthesis of FAS. Our previous studies 10 showed that long-term feeding of Chinese Longjing green tea leaves to rats could reduce their body weight and lipid contents without reducing food intake.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EGCG was also reported to function as antidiabetic. Injection of EGCG into lean and obese Zucker rats significantly lowered blood glucose and insulin levels, and green tea extract increased glucose metabolism in adipocytes (Broadhurst et al, 2000;Kao et al, 2000). Epicatechin, structurally similar to EGCG, is the active compound in the extract from Pterocarpus marsupium Roxb bark traditionally used in Indian folk medicine to treat diabetes (Ahmad et al, 1989).…”
Section: Introductionmentioning
confidence: 99%